'Color' processing in the butterfly visual system. Issue 5 (May 2023) - Kinoshita, Michiyo; Arikawa, Kentaro
Abstract: The swallowtail butterfly, Papilio xuthus, has excellent color discrimination abilities, and its visible light spectrum is notably wide. We discuss the neural basis of color vision in P. xuthus, highlighting some of the evolutionary adaptations in this species in relation to other insects. These adaptations include inter-photoreceptor (PR) interactions that produce spectral-opponent PRs, and complex higher order color-coding neurons.